Prenatal care: satisfaction and expectations - Aliny de Lima Santos; Cremilde Aparecida Trindade Radovanovic; Sonia Silva Marcon (Rev Rene)
The aim of this study was to evaluate the satisfaction of pregnant women with prenatal care, to identify issues they would like to be addressed during the care and the factors that would preclude participation in pregnant meetings. This qualitative study was conducted in Cajazeiras-PB. The data were collected in October 2008 through semi-structured interviews with 12 women. It was observed that although the women were satisfied with the care received, they would like to have more information about physiological changes of pregnancy, labor, delivery, infant care and breastfeeding. The factors that, according to them, could prevent participation in groups of pregnants are: distance, schedule and household chores. It is concluded by the need to offer more guidance during prenatal care that should be consistent with specific features, characteristics and experiences of pregnant women aiming to facilitate their understanding of information and qualify such assistance even more.